2014
DOI: 10.1096/fj.14-251207
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and biochemical profiles suggest fibromuscular dysplasia is a systemic disease with altered TGF‐β expression and connective tissue features

Abstract: Fibromuscular dysplasia (FMD) is a rare, nonatherosclerotic arterial disease for which the molecular basis is unknown. We comprehensively studied 47 subjects with FMD, including physical examination, spine magnetic resonance imaging, bone densitometry, and brain magnetic resonance angiography. Inflammatory biomarkers in plasma and transforming growth factor β (TGF-β) cytokines in patient-derived dermal fibroblasts were measured by ELISA. Arterial pathology other than medial fibrodysplasia with multifocal steno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
80
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(92 citation statements)
references
References 49 publications
1
80
0
2
Order By: Relevance
“…Our WES data are consistent with previous data using direct sequencing reported for an overlapping list of these genes in 47 FMD patients [11]. Interestingly, this study described deep clinical exploration that showed that FMD patients presented in high proportion connective tissue features such as early-onset degenerative spine disease, dural ectasia and mild connective tissue dysplasia [11].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Our WES data are consistent with previous data using direct sequencing reported for an overlapping list of these genes in 47 FMD patients [11]. Interestingly, this study described deep clinical exploration that showed that FMD patients presented in high proportion connective tissue features such as early-onset degenerative spine disease, dural ectasia and mild connective tissue dysplasia [11].…”
Section: Discussionsupporting
confidence: 91%
“…collagens, fibrillins) in the media and an alteration of TGFb signalling are highly suspected. In support of this, a recent study reported features of connective tissue disease and the elevation of transforming growth factor-beta (TGFb)-1 and TGFb-2 in plasma from FMD patients [11].…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations